Critical review of multimorbidity outcome measures suitable for low-income and middle-income country settings: perspectives from the Global Alliance for Chronic Diseases (GACD) researchers - Najma Siddiqi; Meena Daivadanam; J Jaime Miranda; Trishul Siddharthan; John R Hurst; Rajesh Vedanthan; Gary Parker; Gina Agarwal; Shabbar Jaffar; Naomi Levitt; Niels H Chavannes; Pallab K Maulik; et al. (BMJ Open)
Objectives There is growing recognition around the importance of multimorbidity in low-income and middle-income country (LMIC) settings, and specifically the need for pragmatic intervention studies to reduce the risk of developing multimorbidity, and of mitigating the complications and progression of multimorbidity in LMICs. One of many challenges in completing such research has been the selection of appropriate outcomes measures. A 2018 Delphi exercise to develop a core-outcome set for multimorbidity research did not specifically address the challenges of multimorbidity in LMICs where the global burden is greatest, patterns of disease often differ and health systems are frequently fragmented. We, therefore, aimed to summarise and critically review outcome measures suitable for studies investigating mitigation of multimorbidity in LMIC settings.Setting LMIC.Participants People with multimorbidity.Outcome measures Identification of all outcome measures.Results We present a critical review of outcome measures across eight domains: mortality, quality of life, function, health economics, healthcare access and utilisation, treatment burden, measures of ‘Healthy Living’ and self-efficacy and social functioning.Conclusions Studies in multimorbidity are necessarily diverse and thus different outcome measures will be appropriate for different study designs. Presenting the diversity of outcome measures across domains should provide a useful summary for researchers, encourage the use of multiple domains in multimorbidity research, and provoke debate and progress in the field.